Improving the realism of ground movement models - Stergianos, Christofas (2018)
As air traﬃc increases, more airports are facing capacity problems. A growing number of airports are considering optimisation methods as a solution for increasing their capacity and improving their eﬃciency. However, modelling an airport is complicated as there are many processes that happen in parallel, each with different constraints and objectives that need to be considered. This thesis focuses on the ground movement problem, the problem of moving aircraft eﬃciently around an airport. This problem links the problems at the stands and at the runways, and a good model for this problem can not only help the controllers who direct the aircraft to do so more effectively, but can also feed into taxi time estimation improvements, which can aid the solution of other optimisation problems, such as take-off sequencing. Firstly, the effects of the pushback process are investigated and a model that includes this process is presented. Secondly, the effects of different levels of prioritisation between arrivals and departures is investigated. Thirdly, the effects that the airport layout has on the routing process is investigated by examining various airport morphologies and by identifying areas that can cause delays. Different airport morphologies are compared, and the use and importance of alternative paths is highlighted. Moreover, the gate allocation process that also affects the ground movement problem is considered, and a model that uses the routing process of aircraft as a tool to provide a more informed and tailored allocation of aircraft to the gates is presented. A 52% decrease in the duration of delays was observed during the routing process of aircraft when the two processes were integrated. Furthermore, a new routing algorithm that solves the routing problem faster than what is currently used in academia for routing aircraft by taking into consideration all the available paths is presented. The results show a 46% to 67% (depending on the airport) improvement on execution time. Finally, the model is applied in a flight simulator cockpit - a tool for assisting the air transportation operations - and it was integrated with other novel technologies in other research fields. This research provides a more realistic and faster way to solve the ground movement problem of aircraft.